Ecocide as a precursor of a particularly acute and postponed genocide of Ukrainian and European population in 2023 - Kupriianova, Larysa; Kupriianova, Daryna (Journal of Education, Health and Sport, 2023)
In the morning of June 6, 2023, occurred a catastrophe that shook the whole population of Europe as well as one of the whole World. Russian troops blew up the Kakhovka hydroelectric dam, causing the biggest environmental crisis since the explosion at the Chernobyl nuclear power plant. Thousands of victims, and this number is actual exceptionally nowadays without future predictions; hundreds of hectares of land, which were once a fertile base for the world-famous Kherson tomatoes and watermelons, fell victim to the brutality of Russian aggression. Countless species of animals and plants, aquatic and terrestrial, that will never have their natural habitat or merely the second chance in their life again. After surviving the First and the Second World Wars, our historians never get tired of repeating that such disasters are one of the typical tactics of conducting “a brutal war”. After all, no one has yet rejected “the scorched-earth policy” and neither an attack nor a retreat has ever been without such brutality. Why are we raising the issue of the disaster at the Kakhovka hydroelectric dam today? And, even knowing that it is not the first time that such a strategic object becomes a pawn in the brutal plans of Russia? Because this time we are talking about the global ecological and demographic crisis, which, as a middle result, is following the explosion. There are not only thousands of destinies and lives that were mutilated, but also the ecosystem which was destroyed, as well as there are definitely even much bigger consequences that Russia seeks with its attacks, and we are actually going to talk about them in our article.